Consortium for violence prevention research, leadership training, and implementation for excellence (CONVERGE): a protocol to train science leaders in gender-based-violence and violence-against-children research for impact - Yount, Kathryn M.; Comeau, Dawn; Blake, Sarah C.; Sales, Jessica; Sacks, Michael; Nicol, Hannah; Bergenfeld, Irina; Kalokhe, Ameeta S.; Stein, Aryeh D.; Whitaker, Daniel J.; Parrott, Dominic; Van, Hoang Thi Hai (Frontiers in Public Health, 2023)
Background: Gender-based violence (GBV) and violence against children (VAC) are prevalent and interconnected global health challenges, yet data and research capacities to study these forms of violence and to generate evidence-based policies and programs remain limited. To address critical shortages in research capacity in Vietnam and to establish a model for other Low- and Middle-Income Countries (LMICs), we are establishing CONVERGE—the Consortium for Violence Prevention Research, Implementation, and Leadership Training for Excellence. Methods: Based on a needs assessment with partners in Vietnam, CONVERGE will provide a comprehensive research training program supporting 15 long-term, postdoctoral trainees with multi-disciplinary research training in GBV and VAC. We also will offer in-country trainings and short-courses to 40 short-term mid-career academic trainees and 60 short-term practitioner/stakeholder trainees over five years to build productive GBV and VAC academic, scientific, and practitioner networks. The CONVERGE training program has four components: 1) 14 hours of virtual/in-person annual mentorship training to prepare research mentors and to create a pipeline of future mentors in Vietnam; 2) a one-month intensive research training for long-term postdoctoral fellows at Emory University; 3) a structured 17-month, in-country mentored research project for long-term trainees that results in a peer-reviewed manuscript and a subsequent grant submission; and, 4) week-long in-country intensive translational trainings on implementation science, advanced topics in leadership, and advanced topics in science dissemination. Opportunities for on-going virtual training and professional networking will be provided for CONVERGE trainees and mentors in Vietnam with other trainees and mentors of D43s focused on injury/violence prevention, D43s housed at Emory, and D43s with other institutions in Southeast Asia. To assess the reach, implementation, fidelity, and effectiveness of these four components, we will implement a rigorous, mixed-methods, multi-level evaluation strategy using process and outcome measures. Findings from the evaluation will be used to refine program components for future trainee and mentor cohorts and to assess long-term program impact. Discussion: Led by Emory University in the US and Hanoi Medical University in Vietnam, CONVERGE represents leading institutions and experts from around the world, with a goal of providing mentorship opportunities for early-career scientists with an interest in violence prevention.